Changing university in achanging region - Andrey M. Sergeev; Pavel V. Fedorov; Anna V. Gushina (Moscow Polytechnic University, 2022)
The article comprehends the history, modern state and development perspectives of the oldest HEI in the Murmansk region - Murmansk State Humanities University (MSHU). Theauthors reflect on the opportunities of transformation of local universities into the factor of territorial development of Russia, estimate the potential of a humanities university in solving practically oriented tasks, which face a region.